Chronic Disease Management. (11th November 2018) - Xu, B; Cao, G; Han, L; Li, M; Tayie, F; Yao, S
Abstract: An increasing body of evidence suggests an association between fat intake and cognitive function and dementia. There are conflicting results from population-based studies, possibly owing to different methods of assessing fat intake and cognitive outcomes, making it difficult to draw conclusion on this association. Therefore, we conducted a meta-analysis to provide a quantitative synthesis of population-based studies on the relationship between fat intake and cognitive outcomes. PubMed, Embase, PsycINFO and Web of Science databases were systematically searched for papers published before November 2017 that reported an association between fat intake and cognitive outcomes, including mild cognitive impairment, dementia and Alzheimer disease. Data were extracted independently by two researchers. We extracted and pooled adjusted relative risk (RR) values and their corresponding 95% confidence intervals (CIs) from prospective studies. Data were analyzed via descriptive methods and meta-analysis using random-effect modeling. We identified twenty-one cohort studies, and eight were included in this meta-analysis, covering a total of 18, 016 participants. There was a significant association between a decreased risk of mild cognitive impairment and total fat consumption (RR: 0.57, 95% CI: 0.41–0.81), monounsaturated fat consumption (RR: 0.64, 95% CI: 0.46–0.90), and polyunsaturated fat consumption (RR: 0.48, 95% CI: 0.29–0.78), and saturated fat consumption was associated with an increased risk of dementia (RR: 2.15, 95% CI: 1.18–3.91) and Alzheimer disease (RR: 1.87, 95% CI: 1.09–3.20). In conclusion, total fat consumption, particularly of monounsaturated and polyunsaturated fat, decreases the risk of mild cognitive impairment, whereas saturated fat consumption increases the risk of dementia and Alzheimer disease.